Early mobilization is associated with decreased mechanical ventilation and ICU length of stay following cardiac surgery - Raidou, Vasiliki; Dimopoulos, Stavros; Chatzivasiloglou, Foteini; Kourek, Christos; Tsagari, Vasiliki; Pitsolis, Theodoros; Papadopoulos, Kirilos; Kriaras, Ioannis; Tasouli, Androniki; Nanas, Serafeim; Karabinis, Andreas (Health & Research Journal, 2021)
Background: Early mobilization of the Intensive Care Unit (ICU) patients improves muscle strength and functional capacity. It has been demonstrated that prevents Intensive Care Unit Acquired Weakness (ICUAW) and accelerates ICU discharge. However, data on mobilization early after cardiac surgery are inadequate. This study aimed to record early mobilization and investigates the association with ICU findings in cardiac surgery patients. Material and Methods: In this observational study, 165 patients after cardiac surgery were enrolled. Of these, 159 were assessed for early mobilization and mobilization status during ICU stay. Mobilization practices were recorded from 1st post ICU admission and every 48 h until 7th day. The duration of mechanical ventilation (MV) support, ICU length of stay and clinical outcome were recorded from medical records registration. Results: Early mobilization consisted of active and passive limb mobilization, sitting in bed and transferring from bed to chair. The proportion of patients mobilized, was 18% (n = 29/159) on day 1, 53% (n = 46/87) on day 3, 54% (n = 22/41) on day 5 and 62% (n = 15/24) on day 7. ICU length of stay was reduced for mobilized patients (n = 29) on day 1 compared to non-mobilized ones (24 ± 10 vs 47 ± 73 h respectively, P = 0.001). The duration of MV was shorter in mobilized patients on day 3 (n =46) compared to bedridden, (18 ± 9 vs 23 ± 30 h respectively, P = 0.01). Conclusions: Early mobilization after cardiac surgery was found to be low with a significant trend to increase over ICU stay. It is also associated with a reduced duration of MV and ICU length of stay.